Reversible cerebral vasoconstriction syndrome in a methylphenidate-treated patient: a case report - Marie-Noëlle Osmont; Cécile Malrain; Anne-Lise Ruellan; Amine Benchikh; Emmanuelle Herlem; Elisabeth Polard; Lucie-Marie Scailteux (BMC Neurology)
Abstract Background Reversible cerebral vasoconstriction syndrome (RCVS) is characterized by severe headaches, often thunderclap headaches, and a multifocal constriction of the cerebral arteries. Although RCVS can occur spontaneously, some cases occur after exposure to drugs. We describe the first case of RCVS in which methylphenidate, a drug with vasoconstrictive properties, is the only suspected drug. Still an unexpected adverse drug reaction of methylphenidate, and so far observed with the concomitant use of vasoactive drugs and methylphenidate, RCVS can be observed when methylphenidate is used alone. Case presentation A 44-year-old French female presented with sudden onset of severe thunderclap headache during exercise. She had been treated for about 2 years with 54 mg extended-release MPH twice a week for attention deficit / hyperactivity disorder. After clinical, biological and imaging examinations, clinicians concluded to a highly probable RCVS diagnosis, probably linked to methylphenidate use. Major causes of RCVS were ruled out and the methylphenidate treatment was discontinued. The outcome was favourable with nimodipine treatment. We also describe two other cases of methylphenidate induced RCVS recorded in French Pharmacovigilance Database. Moreover, RCVS is an adverse reaction reported more frequently than expected with methylphenidate in the International Pharmacovigilance Database (VigiBase®), suggesting a pharmacovigilance signal. Given its pharmacodynamics, i.e. pre-synaptic dopamine and norepinephrine reuptake inhibition, methylphenidate is theoretically likely to contribute to this vascular event. Conclusions The role of methylphenidate needs to be considered in case of RCVS diagnosis observed in a treated patient. Although the frequency of this potential adverse drug reaction is expected to be rare, clinicians should be aware of its possible occurrence, given the ever-increasing use of methylphenidate.